Implementation internet of things-based catfish aquaculture to measure water quality and minimize pond waste - Rizky Muliani Dwi Ujianti; Setyoningsih Wibowo; Bambang Hadi Kunaryo (Universitas Muhammadiyah Magelang, 2023)
Fisheries aquaculture business really helps the community to improve their economy. This community service activity was carried out at the Lee Kung catfish aquaculture group in RW X, Kembangarum Village, West Semarang District, Semarang City. The aim of this program is to design Internet of Things (IoT) based technology as a solution to reduce catfish pond waste and efforts to prevent stunting by consuming catfish. Implementation of the program is carried out using administrative and e-commerce assistance methods, catfish pond grants accompanied by introduction and assistance in the use of IoT for monitoring catfish pond waste and assistance in preventing stunting by presenting fish nutritional material. The result of this program is increasing skills in using IoT for ponds and digital e-commerce for sales, thereby providing added economic value to cultivators. Apart from that, residents also understand the importance of diversifying food preparations made from catfish as well as providing advice on preventing stunting by consuming fish.